The Influences Of AI To The Gameplay - On, Jia Hao (2020)
Nowadays, AI has played an important role in most video games. The implementation of the AI in the video games that create lots of improvement for the game development which can make the game more enjoyable such as monster move in Monster Hunter, Any Boss Fight in Action or RPG. Different genres have different designs for the AI but AI not only affects the game genre but also affects the difficulty of the game by changing the intelligence of the AI or the status of the AI in the game.